2020
DOI: 10.1038/s41598-020-78031-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolic phenotyping for Alzheimer’s disease

Abstract: Finding early disease markers using non-invasive and widely available methods is essential to develop a successful therapy for Alzheimer’s Disease. Few studies to date have examined urine, the most readily available biofluid. Here we report the largest study to date using comprehensive metabolic phenotyping platforms (NMR spectroscopy and UHPLC-MS) to probe the urinary metabolome in-depth in people with Alzheimer’s Disease and Mild Cognitive Impairment. Feature reduction was performed using metabolomic Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 91 publications
1
24
2
Order By: Relevance
“…Despite insufficient clinical AD data concerning cholesterol metabolites and dicarboxylic acids (DCAs), we observed significantly lower levels of these metabolites after CMA treatment 79 . Levels of pregnanediol, a metabolite of pregnenolone, and DCAs, end-products of β -or omega oxidation, which were observed as decreased in the present study, were previously reported to be lower in the urine of patients with AD 80,81 . Considering the neurotoxic role of bile acids, along with the oxidative properties of DCAs, the detection of decreased levels of bile acid metabolites and DCA products in the present study is therefore not surprising.…”
Section: Discussionsupporting
confidence: 74%
“…Despite insufficient clinical AD data concerning cholesterol metabolites and dicarboxylic acids (DCAs), we observed significantly lower levels of these metabolites after CMA treatment 79 . Levels of pregnanediol, a metabolite of pregnenolone, and DCAs, end-products of β -or omega oxidation, which were observed as decreased in the present study, were previously reported to be lower in the urine of patients with AD 80,81 . Considering the neurotoxic role of bile acids, along with the oxidative properties of DCAs, the detection of decreased levels of bile acid metabolites and DCA products in the present study is therefore not surprising.…”
Section: Discussionsupporting
confidence: 74%
“…The largest metabolic analysis performed on urine of AD and MCI patients have permitted to shape a urinary metabolic phenotyping. Urine contains metabolites that reflect a response to injury, including OS, occurring at high distance or carry information originated from the gut microbiome, a novel area of research in neurodegeneration and AD [ 138 ]. The strength of this report, even if not specific on oxidative markers, lies in the potential to shape a metabolic profile associated with AD and to correlate such metabolites to genetic variants [ 138 ].…”
Section: Products Of Oxidative Damage In Blood Csf and Other Body Fluids Of Ad Patientsmentioning
confidence: 99%
“…Urine contains metabolites that reflect a response to injury, including OS, occurring at high distance or carry information originated from the gut microbiome, a novel area of research in neurodegeneration and AD [ 138 ]. The strength of this report, even if not specific on oxidative markers, lies in the potential to shape a metabolic profile associated with AD and to correlate such metabolites to genetic variants [ 138 ]. Peña-Bautista and colleagues have recently developed some analytical methods to determine a panel of lipid peroxidation biomarkers in urine, plasma, and saliva samples [ 25 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ].…”
Section: Products Of Oxidative Damage In Blood Csf and Other Body Fluids Of Ad Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics is expected to provide new insights into biomarkers for the diagnosis and prognosis of AD [ 27 , 77 , 85 ]. As a conventional metabolomics research object, urine has also been analysed in metabolomics studies of AD, and characteristic urinary metabolites were identified and considered potential biomarkers of AD [ 36 , 83 ]. The analysis technology based on gas chromatography-mass spectrometry (GC–MS) with high sensitivity, high resolution and high reproducibility has been widely used in metabolomics studies.…”
Section: Introductionmentioning
confidence: 99%